(untitled) (The Pakistan Development Review, 2016)
In this study, we examine the hold-up problem under price cap regulation in developing economies characterised by high inflation that have a limited ability to commit. The governments of developing countries are unable to modify the exact inflation rate. If high inflation is brought about by unexpected monetary expansion after the initial average price is fixed, the insufficient ability to show exact inflation causes a lack of commitment to adjust the initial fixed price to the modified price. The study’s findings show that those that have a limited ability to commit cause a hold-up problem if inflation is sufficiently high for a firm to stop production at the initial price, while the hold-up problem does not occur if inflation is lower and the initial fixed price generates a sufficient profit for the first-best investment for the firm. JEL Classification: D86, L14, L43,L51 Keywords: Price Cap Regulation, Hold-up Problem, Limited Ability of Commitment, Inflation Adjustment